Correlation of quality characteristics of lubricating greases that have rheological nature - Манойло, А.М.; Зеленина, А.И.; Терещенко, В.А. (Proceedings of National Aviation University (archive), 2009)
Descriptions of quality of greasings|grease|, having reologycal| nature are considered in the article. The recommended sequence of leadthrough of works|wrk| is offered on drafting|composition| of equalizations|equiponderate| of regression.